KONDISI HIDROGEOLOGI DAERAH BUMBUNGON, KECAMATAN DUMOGA, KABUPATEN BOLAANG MONGONDOW, PROVINSI SULAWESI UTARA - Jufri, S. F. T.; Utomo, A. P. (LPPM Universitas PRISMA, 2023)
Water is a transparent substance in the form of a liquid that forms rivers, lakes, seas and rain and is the main element in human life. Without water, various life processes for animals, plants and humans would not be possible taking place. This research aims to determine the geological and hydrogeological conditions in the Bumbungon area, District Dumoga, Bolaang Mongondow Regency, North Sulawesi Province. Next, researchers observed the well distribution points forused in making well distribution maps. The well distribution points are made into a map of the distribution of ground water levels (MAT) with the Inverse Distance Weighted (IDW) method. In this research, subsurface data analysis was also used to determine subsurface geology. The groundwater level is calculated based on the land surface elevation minus the value with the depth of the ground water table. The direction of groundwater flow can be determined from the groundwater level contour. Result of MAT measurements at 25 well points in the research area were 0.9 - 6.8 meters. Therefore, groundwater flows in regional areas research flows southwest, east, and southeast. From the results of correlation of subsurface data in the research area has 2 types of groundwater aquifer systems, namely free groundwater with a depth of up to (0-6) meters and groundwater aquifer systems depressed, with a depth of up to (20-30) meters below the surface. The recharge area in the research area is located at the northwest and southeast areas of the research area and the discharge area or discharge area is in the middle of the research area, namely on (Dumoga River), and has a local groundwater flow system.